STUDY OF MAPPING THE NEEDS OF FACILITIES AND INFRASTRUCTURE OF AUTOMOTIVE BOARD OF UNIVERITAS PENDIDIKAN INDONESIA - Muhidin, Asep; M N, Ridwan Adam; Mubarak, Ibnu (Journal of Mechanical Engineering Education, 2020)
Facilities and infrastructure are one of the supports in the educational process, the completeness of facilities and infrastructure can affectthe learning outcomes of students. However, the inadequacy of existing facilities and infrastructure with standards is a problem that needs to be resolved. The purpose of this study is to find out the existence of mapping thatis in accordance with the needs of practicum facilities and infrastructure, to know the mapping technique for practicum facilities and infrastructure needs, and to know the description of the results of the mapping of practicum facilities and infrastructure needs at the Automotive Body Workshop Universitas Pendidikan Indonesia. The benefit of this research is to provide information to the head of the institution that in the educational process, complete learning facilities and infrastructure are needed so that students' competencies and achievements can be developed, provide input for the institution in order to meet the needs of available learning facilities and infrastructure in order to develop competence and achievement of participants. students in academic and non-academic aspects. This research method uses qualitative methods with descriptive approaches, data collection techniques in the form of interviews, observation, and documentation. The data analysis technique used in this research is using the Spradley model data analysis. The results showed that there was no mapping of the facilities and infrastructure needs of the Automotive Body Workshop Universitas Pendidikan Indonesia, and did not refer to any policies or standards, the practicum facility and infrastructure needs mapping technique used several stages, namely data collection (interviews, observation and documentation), then in the analysis of the analysis as needed by analyzing the Spradley model data, then mapping the form of tables and pictures, mapping the needs for facilities and infrastructure including facilities in the form of furniture, equipment and materials, infrastructure in the form of a practicum area / space in the form of a design area, a formation area, a body repair area , painting area, instructor room, and storage room.